Unveiling The Impact of Logistics Service Quality On Customer Satisfaction and Demographic Factors As Moderator: Indonesia Quick Commerce Perspective - Gusti Ayu Made Hanny Dian Savitri; Erlinda Nusron Yunus; Alain Widjanarko (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Quick commerce is one of the biggest opportunities in the COVID-19 pandemic. In Indonesia, quick commerce has increased due to the trend of purchasing groceries online. Even though shopping activities are shifted online, customers still demand a service as excellent as they would order at a physical store.Purpose: This study aims to determine the factors of logistics service quality that improve customer satisfaction and examine the demographic factors that enhance the relationship between logistics service quality and customer satisfaction.Design/methodology/approach: This study employed a survey method to achieve broad data coverage. The data analysis techniques used in this study included hierarchical regression analysis and moderated regression analysis (MRA).Finding/Results: The findings show that logistics service quality positively affects customer satisfaction for quick commerce on Java. This also indicates that age is a significant moderating variable in the relationship between logistics service quality and customer satisfaction.Conclusion: Quick commerce companies should focus on younger customer satisfaction levels. Moreover, companies can increase customer satisfaction based on several logistics service quality factors, such as arranging courier training regarding how to treat customers, providing recommendations for similar products if a particular product is not available, or ensuring that the order will arrive in the customer’s hands in a short time and safely. Originality/value (state of the art): One of the important factors that could be a competitive advantage for a company is logistics service quality; however, research related to quick commerce in an emerging economy is still limited. This research enriches studies related to customer satisfaction, logistics service quality, and demographic factors (gender, age, and income level) by analyzing the perceptions of quick commerce customers. Keywords: demographic factors, logistics service quality, quick commerce, physical store, customer satisfaction